(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The research promotes a discussion about gender-racial discrimination in an attempt to understand its construction and the way in which it is presented, and sexism based on supremacist thinking based on sex (male and female) is aggravated when the racial factor is present. With critical analysis, the work focused on the legal precept of formal equality, determined by the constituting legislator, compared to the reality experienced by black women, especially when she experiences the experience in prison, in order to highlight the disparity of the factual situation in relation to assecuratory devices. . The work demonstrated that the State as guarantor of equal protection, as well as responsible for the educational promotion of the penalty and also for the effectiveness of decriminalization, does not fulfill its role whereas more than 1/3 of the women in prison - mostly black, do not have judgment. The methodology to be used in the present work is perfect in the literature review and hypothetical deductive, adopting structural racism as a starting point in view of the incarceration of black women.